2020
DOI: 10.1017/s095977432000044x
|View full text |Cite
|
Sign up to set email alerts
|

‘I Have Done Hundreds of Rock Paintings’: On the Ongoing Rock Art Tradition among Samburu, Northern Kenya

Abstract: In this paper, we discuss observations from fieldwork in northern Kenya which revealed solid evidence for a vital ongoing rock art tradition among warriors of Samburu—lmurran. They make rock art during their lives as warriors, typically between the ages of 15 and 30, when they live away from their villages, herding cattle and thus representing a specific ‘community of practice’. Our findings reveal that Samburu rock art is made predominantly as a leisure occupation, while camping in shelters, as part of activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Furthermore, he asked if taking animism seriously involves not taking it too seriously (Willerslev 2013), as he observed that important aspects of the animistic cosmologies of the Siberian Yugakirs is laughter, irony and ridicule towards the spirits. Interesting are also the responses given in interviews with practitioners of traditional and ongoing rock art production among Samburu in Kenya (Goldhahn et al 2021). Ceremonial and ritual activities were described, but the creation of the art was not part of it, it was on the contrary considered as a recreational activity during stays away from the village while herding cattle.…”
Section: Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, he asked if taking animism seriously involves not taking it too seriously (Willerslev 2013), as he observed that important aspects of the animistic cosmologies of the Siberian Yugakirs is laughter, irony and ridicule towards the spirits. Interesting are also the responses given in interviews with practitioners of traditional and ongoing rock art production among Samburu in Kenya (Goldhahn et al 2021). Ceremonial and ritual activities were described, but the creation of the art was not part of it, it was on the contrary considered as a recreational activity during stays away from the village while herding cattle.…”
Section: Alternativesmentioning
confidence: 99%
“…Comparisons with contemporary rock art 'ethnographies' (e.g. Alberti and Fowles 2018, Nash 2010, Goldhahn et al 2021, as well as insights from thoughts on nonhumans or objects (Domanska 2006, Petursdottir 2012), the strange (Farstadvoll 2019), 'problematic stuff' (Büster 2021), the apparently 'meaningless' (Olsen 2011), on wonder (Stengers 2011) and, in this context, perhaps especially on art (Porr 2019), may generate novel approaches and appreciations of rock art. If it is possible to take it as far as envisaging that some or even all of the Alta rock art were made for no consequential reasons, outside a formal and symbolic frame of reference, is it not too simple an approach to make sense of the past?…”
Section: Alternativesmentioning
confidence: 99%